Evaluasi Program Keluarga Berencana dan Kesehatan Reproduksi Tentang Kasus Peran Serta Pria di Kecamatan Semarang Barat - Purwinarti, Maria Louisa Dwi Hapsari; Rengga, Aloysius; Subowo, Ari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Male participation is a sub program of Family Planning and Reproductive Health Programs. By the perspective result of this program is stagnant. Female contraception still dominated until now. The expectation of male participation for a gender equity between male’s role and women’s role. Evaluation of Public Policy is needed to prevent a baby boom thus a complicated social problems.